Brisbane burns : how the great fires of 1864 shaped a city and its people - Merkley, Sharyn (Samford Valley, QLD : Australian Academic Press Group Pty. Ltd., 2017)
1864 was a tough year for the fledgling town of Brisbane as it struggled to throw off the shackles of its origins as a harsh penal settlement. Commerce was vital to this northern outpost and its heart beat along Queen Street - a rough dirt track lined by deep open drains and constantly rutted by the busy traffic of horse drawn vehicles. Two devastating fires, one in April and the second, and worst, in December, swept through the commercial hub. Nearly 70 shops, offices and homes in Queen, George, Elizabeth and Albert Streets were destroyed, a terrible blow to the growing community. This book is the dramatic, uplifting, at times heart-wrenching, historical record of those who saw their dreams and hopes reduced to ashes, yet survived to lay the foundations of the booming sub-tropical metropolis that today is Australia's third biggest city. It brings to light the stories of both the ordinary and well-known citizens of early Brisbane whose lives were touched by the fires. Each personal story is connected by the timeline and path of the fire as it engulfs then consumes buildings, homes, shacks and livelihoods. Here is central Brisbane, 1864, consumed by fire but alive with the family histories of such varied workers as drapers, butchers, jewellers, saddlers, politicians, policemen, hairdressers, publicans and ex-convicts to name a few.
Includes bibliographical references (pages 245-248)
Keywords: Fires -- Queensland -- Brisbane -- History -- 1851-1891.; Disasters -- Queensland -- Brisbane -- History -- 1851-1891.; Business enterprises -- Queensland -- Brisbane -- History -- 1851-1891.; Queen Street (Brisbane, Qld.) -- History -- 1851-1891.; Brisbane (Qld.) -- History -- 1851-1891.; Australian